2020
DOI: 10.3904/kjim.2019.444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcineurin inhibitor on post-endoscopic retrograde cholangiopancreatography pancreatitis in patients with liver transplantation: a propensity-matched cohort study

Abstract: Background/Aims: A calcineurin inhibitor may alter pancreatic function and inflammatory reaction. This study aimed to determine the possible pharmacologic effect of the calcineurin inhibitor, tacrolimus, on pancreatic function, and to determine its preventive effect on post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis in liver transplantation (LT) patients. Methods: The serum amylase and lipase values before and after LT were compared. The frequency of post-ERCP pancreatitis was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…5 After that, a calcineurin inhibitor, tacrolimus, has been suggested based on several previous preclinical and clinical studies. [6][7][8] Rao et al 9 reported the results of a prospective pilot study that compared the PEP rate of the tacrolimus group and control group based on this recent emerging evidence. In this study, the authors reported that the incidence of PEP was reduced by nearly 50% in the tacrolimus group compared with that in the control group (8.3% vs. 15.7%).…”
mentioning
confidence: 99%
“…5 After that, a calcineurin inhibitor, tacrolimus, has been suggested based on several previous preclinical and clinical studies. [6][7][8] Rao et al 9 reported the results of a prospective pilot study that compared the PEP rate of the tacrolimus group and control group based on this recent emerging evidence. In this study, the authors reported that the incidence of PEP was reduced by nearly 50% in the tacrolimus group compared with that in the control group (8.3% vs. 15.7%).…”
mentioning
confidence: 99%